2021
DOI: 10.1037/pst0000371
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of change in patient treatment outcome expectation during cognitive-behavioral psychotherapy for generalized anxiety disorder.

Abstract: Positive patient-rated psychotherapy outcome expectation at pre- or early treatment is associated with posttreatment improvement. However, there is limited research on patients’ change in outcome expectation across therapy and participant factors that predict both pretreatment outcome expectation and expectation change. The present study aimed to examine (a) the overall trajectory of change in patients’ outcome expectation from pretreatment through treatment’s end; (b) baseline patient characteristics as predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…[38][39][40] Some studies analysed the relationship between initial expectation change and treatment outcome. [41][42][43] As already mentioned above, initial positive outcome expectations are associated to a better treatment outcome, whereas inducing positive outcome expectations or changing negative ones change significantly the treatment outcome in a positive way. Thus, expectations play a central role in psychotherapy, regarding the therapy outcome 44 45 or the therapeutic relationship.…”
Section: Open Accessmentioning
confidence: 77%
“…[38][39][40] Some studies analysed the relationship between initial expectation change and treatment outcome. [41][42][43] As already mentioned above, initial positive outcome expectations are associated to a better treatment outcome, whereas inducing positive outcome expectations or changing negative ones change significantly the treatment outcome in a positive way. Thus, expectations play a central role in psychotherapy, regarding the therapy outcome 44 45 or the therapeutic relationship.…”
Section: Open Accessmentioning
confidence: 77%
“…Although extensive research investigating patients' initial SE (Clarke et al, 2014 ; Keshen et al, 2017 ; Pinto et al, 2008 ) and OE (Constantino et al, 2018 ) levels exists, there is limited information on how these patients' cognition change during treatment, especially the change in SE (for a discussion on change in OE in the current sample, see Vîslă et al, 2021 ). In the present study, we found that SE improved during CBT treatment for GAD, which is consistent with the results of two other studies that investigated SE change during treatment (Brown et al, 2014 ; Keshen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 95%
“…The possible score range for this subscale is from 4 to 20, with higher scores reflecting more positive OE or hope for improvement. PATHEVH demonstrates satisfactory reliability in patients with depression and anxiety (Schulte, 2005 ; 2008 ; Vîslă et al, 2019 ; Vîslă et al, 2021 ). The internal consistency for the current sample was α > 0.76.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations